Unraveling the Use of Quantity Maxim among EFL Learners on Online Classroom Interaction - Dewi, Mercya Christ Sita; Indriani, Lilia (New Language Dimensions, 2020)
This naturalistic qualitative study is intended to unravelling the working of quantity maxim introduced by Grice (1975) on EFL online classroom interaction amid the Covid-19 pandemic. Besides, this study is designed to investigate whether or not students violating or obeying the quantity maxim by observing and unravelling the utterances produced during online classroom interaction. Moreover, this study also provides factors that influence the non-observance maxim of quantity. The participant consists of 31 students from the fifth semester majoring in English Education at Tidar University. The study is conducted by recording, transcribing, and classifying the conversations done on online classroom interaction, viewed from Gricean maxim perspectives. The results reflect that students both observed and violated the maxim of quantity. The total number of observance maxim is 9, and 14 for the non-observance maxim. This study brings the conclusion that external factors such as unstable internet connection and interference coming from the surrounding environment during the online classroom can cause EFL students to break the maxim of quantity principle. Meanwhile, anxiety as an internal factor plays a crucial factor that leads the EFL students to violate the quantity maxim.